Effects of obesity on functional capacity. (13th August 2013) - Pataky, Zoltan; Armand, Stéphane; Müller‐Pinget, Solange; Golay, Alain; Allet, Lara
Abstract : Objective: To assess the relationships between BMI and walking speed, balance control, sit‐to‐stand performance (a measure of mass specific lower limb power), and endurance. Design and Methods: Thirty‐six women with a BMI ≥ 30 kg/m 2 and 10 women with normal body weight (BMI between 18 kg/m 2 and 25 kg/m 2 ) were enrolled in this observational study. The obese group comprised 12 persons with a BMI ≥ 30 and <35 (obese), 14 subjects with a BMI ≥ 35 and <40 (severe obesity) and 10 people with a BMI ≥ 40 kg/m 2 (morbid obesity). All subjects underwent a clinical examination, a gait test, an endurance test (6 minutes walking test), a mass specific lower limb power test (five times sit‐to‐stand) and a balance test. Results: Obese women exhibited slower fast gait speeds ( P < 0.05) with correspondingly shorter stride lengths, poorer sit‐to‐stand performance ( P < 0.05), and endurance ( P < 0.05). However, once the state of severe obesity was reached, additional weight gain (morbid obesity) does not seem to decrease these functional capacities any further. Conclusion: This study underlines the importance of assessing obese patients' related physical problems in an early stage of obesity in order to focus exercise regimens and promote appropriate health behaviors.